Exploring barriers for trachomatous trichiasis surgery implementation in gamo zone, Southern Ethiopia. - Chuchu Churko; Mekuria Asnakew Asfaw; Zerihun Zerdo (Public Library of Science (PLoS), 2021)
Background Trachomatous trichiasis is the leading infectious cause of blindness worldwide. The World Health Organization recommends eyelid surgery to reduce the risk of visual impairment from trichiasis. Unfortunately, the number of cases operated has grown less than expected. An understanding of barriers is fundamental for instituting measures to increase surgical uptake. Therefore, the aim of this study was to explore barriers of TT surgery implementation. Methods A qualitative study design was employed in December 2019. Purposive sampling technique was used to select three districts from Gamo zone, Southern Ethiopia. We conducted 9 FGDs and 12 in-depth interviews. Data was collected by audio tape recorder in Amharic and Gamogna languages and then transcribed to English language. The recorded interviews and focus group discussions were transcribed to verbatim (written text) and thematic analysis was done manually and reported accordingly. Findings we explored a number of barriers that hindered implementation of trichiasis surgery. The recurrence of trichiasis after surgery was the main challenges faced by operated individuals. The other barriers reported are negative perception towards trichiasis surgery, lack of logistic and supplies, transportation access problem for remote communities, inadequate trained health professional, less commitment from higher officials, lack of interest of integrated eye care workers due to incentive issues, believes of patients waiting supernatural power for healing service and carelessness of patients to undertake operation. Conclusion and recommendation Post-surgical trichiasis, lack of commitment from government officials and negative perception of patients towards the disease were considered as the reported barriers for implementation of trachomatous trichiasis. Closely supervising the integrated eye care workers would be the first task for district health offices to increase the uptake and improve the quality of service. Logistics and supplies should be made available and adequate to address all affected people in the community.